The Netflix Effect in the Age of Video on Demand Services - Sedat ÖZEL (İnsan&İnsan Bilim Kültür Sanat ve Düşünce Dergisi, 2020)
The emergence and development of video streaming technology has been the reason for a strong change in traditional television production and consumption forms. An active viewing process for the audience is frequently mentioned, also new opportunities and new business models in the distribution of television content are emphasized. The study focuses on OTT, one of these business models, together with It examines the basic codes of change adhering to a conceptual analysis. The Netflix effect statement is often used to describe this change. In this context, the determinations of how Netflix stands out are at some point a concrete example of the change in television. Netflix has grown globally with developing content catalogs that fit the fragmented structure of the audience, implementing its own broadcast plan against the standard television stream, and strategies that support the binge watching behavior associated with them.